The percentage of the contribution of the sovereign style to learning and thinking by performing the handstand skill among secondary school students (Journal of the College of Basic Education, 2024)
Handstand is a technical and physical challenge that requires high physical fitness, excellent balance and precise movement control. It is as one of the most prominent gymnastics skills that combine motor challenge, skill performance, mental ability and. Understanding the different methods of learning and thinking and applying them in learning is one of the most effective solutions in learning as there is a concept of control and sovereignty or cerebral dominance as the research aims to understand how the prevailing patterns of learning and thinking affect the ability of students to learn and develop the skill of handstand and highlights the problem of research in the difficulty of finding an appropriate preference for each skill and returns A large part of the misunderstanding to the use of one particular pattern of thinking and the assumption that all students use this pattern and not others The researcher relied on the descriptive approach in the style of correlational relations and determine the research community of secondary school students in Baghdad and the researcher built a measure of the sovereign pattern in learning and thinking and used a handstand skill test for fourth grade students and concluded that the percentage of students' use of the prevailing pattern of learning and thinking for the right style (36.5%) and the left (33.2%) A..And the shares of the variable (right pattern), with the highest percentage contribution of the skill of handstand